Hubungan Pengetahuan Dan Dukungan Suami Dengan Pemanfaatan Layanan Antenatal Care Di Rumah Sakit Siti Aisyah Lubuklinggau Tahun 2025 - Rena Putri Sari; Sasteri Yuliani; Nuche Marlianto (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Globally, although 88% of pregnant women access antenatal services with skilled health personnel at least once, only two out of three (69%) receive four antenatal care visits. In Southeast Asia, the coverage of K1 visits reaches 85%, but K4 visits only reach 55%. The purpose of this study is to determine the relationship between knowledge and support from husbands and the use of antenatal care services by pregnant women at Siti Aisyah Hospital in Lubuklinggau in 2025. The research method used was descriptive quantitative with a cross-sectional approach, using the chi-square statistical test. The sampling technique used was purposive sampling with a sample size of 32 people at Siti Aisyah Hospital in Lubuklinggau. The results of the univariate analysis showed that a small number of respondents (21.9%) had insufficient knowledge, almost half of the respondents (37.5%) had unsupportive husbands, and almost half of the respondents (34.4%) did not fully utilize antenatal care services. The results of the bivariate analysis showed a relationship between knowledge (0.0005) and husband support (0.000) with the use of antenatal care services among pregnant women. There is a relationship between husband’s support and knowledge with the use of antenatal care services among pregnant women at Siti Aisyah Hospital in Lubuklinggau in 2025. The results of this study can be used as guidelines for implementing activities at the hospital, including guidance, coaching, and counseling programs on the use of ANC (antenatal care) services.